The Development of Learning Management Activities using the Problem Based: Organic Chemistry to Promote Problem-Solving Skills and Achievement for Students in Senior High School (Matthayom 6): The Development of Learning Management Activities using the Problem Based: Organic Chemistry to Promote Problem-Solving Skills and Achievement for Students in Senior High School (Matthayom 6) - Jinaei, Suntreeya; หมอสินธุ์ ภานุมาศ (RATANABUTH JOURNAL, 2023)
The aimed of this research was to study the efficiency of problem-based learning activities and study the results of operations by comparing after implement the problem-based learning activities to learning achievements of Matthayom 6 students on organic chemistry with the criteria of 75 percentage. A two operation consisting of 1) creating and finding the efficiency of problem-based learning activities, and 2) studying the results of using problem-based learning activities of organic chemistry for Matthayom 6 students. The sample were 30 students in Matthayom 6/1 by group selection. The experiment was conducted for 5 weeks. Data were analyzed by means, standard deviation and one sample t-test. The research founded as follows: 1) Problem-based learning activities on organic chemistry that promote problem-solving skills and academic achievement for Matthayom 6 students, there were including rational, principles, aims, content, structure of activities, activities, media and learning resources, measurement and evaluation, and user manuals. There was consists of objectives, components, guidelines for use, teacher and student roles, activity structure, activity plan, measurement and evaluation tools. The activities and manuals were appropriate at the high level ( = 4.25) and the effective were 76.67/77.43. Moreover, the (2) the students’ post-learning achievement was higher than the criterion of 75 percent with a statistical significance at the .05 level and had problem-solving skills after learning at a high level ( = 4.02).